The Employment of Bioterrorism in International Relations - A Study of Challenges and Ways of Confrontation - Assistant Professor, Dr. Dina Muhammad Jabr,; مدرس دكتور إسماعيل ذياب خليل, , Lecturer, Dr. Ismail Diab Khalil (The college of law and political science journal, 2023)
The Employment of Bioterrorism in International Relations - A Study of Challenges and Ways of Confrontation